KAJIAN PERESEPAN OBAT ANTIHISTAMIN PADA PASIEN RAWAT JALAN DI SALAH SATU RUMAH SAKIT DI BANDUNG - Lisni, Ida; Anggriani, Ani; Puspitasari, Regina (Jurnal Riset Kefarmasian Indonesia, 2020)
Histamine is one of the factors that cause acute and chronic disorders, so it is necessary to investigate further the mechanism of antihistamines in the treatment of allergic diseases. Antihistamines are substances that can reduce or block the effects of histamine on the body by blocking histamine receptors. Antihistamines are one of the drugs that are often prescribed to children to the elderly. Thus the application of therapy in medicine is needed to ensure the use of appropriate drugs to prevent the occurrence of medication errors so that the goal of therapeutic effectiveness can be achieved. The purpose of this study was to determine the prescribing pattern of antihistamine drugs and assess the accuracy of the administration of antihistamines based on dose accuracy and potential drug interactions. Prescribing studies of this drug are descriptive quantitative and qualitative by using data sources in the form of patient prescription sheets taken retrospectively. The results of quantitative research data show that patients 57.23% were female, the highest age was 55-59 years old 12.26%, the most widely used drug was setirizine 72.48%, dose accuracy 89.60% and more doses 10.40%, the potential for drug interactions occurred in 27.83%, The drug that has the most potential for interaction is setirizine with theophylline.